Bivši borci z duševnimi motnjami - Kostnapfel, Janko (Obzornik zdravstvene nege, 1979)
Five years after the basic study on »War as the Triggering Cause of Psychic Disorders of Ex-Fighters« had been carried out, two random samples of 60 patients-veterans (basic group) and 60 patients who had not been engaged in the partisan liberation war (control group) were re-analyzed. Both groups were compared referring to the state of health of patients (horizontal comparison). Followed the comparison between the present state of health and that assessed 5 years ago (vertical comparison). The obtained results were statistically evaluated. Our catamnestic study revealed that within the last 5 years (i. e. up to April 30, 1976), the health status (mental, somatic and social) of the psychiatric patients-veterans had improved and stabilized as compared to the controls. The degree of improvement was observed to have exceeded the anticipated betterment suggested by the basic study.